Comparison of Calcofluor White M2R fluorescence and modified Gram chromotrope Kinyoun staining methods for the detection of microsporidial spores from stool samples - Ithnin, Nur Raihana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Routine diagnosis of intestinal microsporidiosis in clinical diagnostic laboratories relies mostly on detection of microsporidial spores via special staining and microscopic techniques. This paper describes the comparative evaluation of Calcofluor White M2R method, with modified Gram-chromotrope Kinyoun method as the reference standard. One hundred and six stool samples were examined for the presence of microsporidial spores. Sensitivity, specificity, positive and negative predictive values of the Calcofluor White M2R method compared to the reference technique were 95.2%, 4.3%, 78.2% and 20.0%, respectively. The positive predictive value (PPV) was 78.2% and the negative predictive value (NPV) was 20.0%. Despite low specificity of the CFW method due to its ability to stain chitinous wall of microorganisms, the presence of distinct deep-blue horizontal or equitorial stripes in microsporidial spores in modified Gram-chromotrope Kinyoun would likely reduce the false positive results obtained in the Calcofluor White M2R. Hence, the simultaneous use of these two methods would give better performance and accuracy for the detection of microsporidial spores in patients with intestinal microsporidiosis.